Análisis del gasto del gobierno nacional realizado en la región Loreto, periodo 2013 - 2017 - Bustamante Varela, Víctor Abraham (2020)
The reduction of oil production in Loreto brought about the transfer of resources for oil fees and oil surcharges to the Regional Government, local governments, university, etc., which resulted in a stoppage of public works; In this sense, the National Government is called to provide the necessary resources. The objective of the thesis is to analyze the expenditure of the National Government carried out in the Loreto region, in the 2013-2017 period. For this, this research was carried out, which, by its nature, is of Quantitative type, Descriptive level and Non Experimental design. Taking into account the results obtained, it can be seen that the expenses of the National Government executed in the Loreto region were variable, when the ideal would have been to increase year by year. The expenditure consisted of two major items: current expenses, and capital expenses. The analysis shows that the majority of the expenditure was concentrated in Current Expenses amounting to S /. 4,125.95 million equivalent to 77.87% of the total; On the other hand, Capital Expenditures totaled S /. 1,172.67 million representing 22.13% of the expense. Current expenses were concentrated in the Personnel and Obligations item that was S /. 1,751.58 million (42.45% of total current expenditure), while those of capital did so in Acquisitions of Non-Financial Assets with the amount of S /. 922.84 million (78.70 of total capital expenditure).